Developmental competence of goat oocytes vitrified at immature and mature stage in comparsion to fresh oocytes after in vitro fertilization using cauda epididymal spermatozoa - KUMARI, DIMPLE; KUMAR, DHARMENDRA; RAHANGDALE, SANDEEP; JEENA, LALIT MOHAN; SINGH, AJIT PRATAP; SARKHEL, BIKASH CHANDRA (The Indian Journal of Animal Sciences, 2017)
The oocytes were cryopreserved at 2 developmental check points, viz. immature and metaphase II stage, and the outcome of in vitro fertilization (IVF) was assessed as compared to fresh oocytes. The oocytes were cryopreserved by solid surface vitrification technique using equilibration media (4% ethylene glycol) followed by vitrification media (0.5 M sucrose + 35% ethylene glycol + 0.5% polyvinyl pyrollidone). The mature oocytes were pre-treatedwith cytochalasin B for 30 min before vitrification. The vitrified-thawed oocytes of both groups as well fresh oocytes were fertilized with buck epididymal sperm. The results revealed a significantly higher rate of embryonic development in vitrified-thawed immature oocytes as compared to that in vitrified-thawed mature oocytes at all the embryonic stages. The embryonic developmental rate under fresh oocyte group was significantly higher than both vitrified groups. Results indicated that the immature goat oocytes could be a better candidate for long term storage of female germplasm as well as dissemination into distant places.